Pengaruh Strategi Promosi terhadap Peningkatan Volume Penjualan pada CV Karya Abadi Simo Kwagean - Maula Nasrifah (Fakultas Ekonomi dan Bisnis Islam, 2017)
Sales will not be realized without the sale because it CV Karya Abadi doing promotional strategies Advertising and personalselling to increase sales volume. This study aims to determine the will campaign through advertising and personal selling affects sales volume in C.V. Karya Abadi. To achieve these objectives the researchers first conducted a survey in order to identify any variable-variable being considered. In this study, there are three variables: the volume of sales, Advertising and Personal selling. Sempel method used is porposif sampling (sampling technique with a certain considerations). Lagsung to the data obtained from studies in CV Karya Abadi un structure through interview, observation and documentation and analysis using the significance test of each coefficient and significance test models with SPSS version 10.01. From the statistical results can be seen that the value of F> F table (76, 909> 3.3541) then the independent variable (advertising and personal selling) no significant effect so H0 and H1 accepted. To test Thitung on advertising: 2.239 and personal selling: 11.104 and to Ttabel advertising and personal selling is +2.0518 it shows Thitung> Ttabel that H0 rejected and H1 accepted. It can be concluded that the strategy of promotion (advertising and personal selling) affect the volume of sales in C.V. Abadi works by 83.1%, while 14.9% are influenced by other promotional strategy.